Effects of RMB Exchange Rate Fluctuation on China’s Foreign Trade - , Hui Gao (Archives of Current Research International, 2015)
A steady and sustaining development of international trade is an important guarantee for a country to achieve the economic improvement. As a significant tool, exchange rate plays an important role in achieving the balance of one country’s economy and steady development. It also affects a country’s international trade. Due to which, the relationship between exchange rate and trade is widely studied by researchers. The present study is an attempt to study this relationship for China under the time-series framework and provide noteworthy policy implications.